Analisis Penerapan Model Hannafin and Peck sebagai Pendekatan Desain Pembelajaran yang Interaktif dalam Pembelajaran Pendidikan Agama Islam di SMK - Dahmayanti, Siti; Nugraha, Mulyawan Safwandy; Tarsono, Tarsono (ISLAMIKA, 2024)
A good learning design can make a learning process successful, with the learning design the teaching and learning process in the classroom becomes clear and directed. But in fact, there are still students who are less able to play an active role in the learning process as well as students who lack motivation to learn so that they often skip class. Therefore, the purpose of this research is to analyze the application of the Hannafin and Peck model in overcoming these problems. This research uses a qualitative approach with a descriptive model. Data collection techniques used observation, interviews, and documentation. The result is the use of the Hannafin and Peck model in PAI learning can be effective in involving students, making students active and student learning outcomes can be above KKM. In conclusion, the Hannafin and peck learning model has a positive impact on students at SMKN Sukasari.